A CONTRASTIVE STUDY OF DEMONSTRATIVE PRONOUN IN ENGLISH AND JAPANESE - Ade Irma Suryani (STKIP Bina Bangsa Meulaboh, 2014)
This article is a research report which consists of discussion of the various kinds, functions, and position of demonstrative pronouns in English and Japanese. In this article we would like to introduce what are the demonstrative pronoun in English and Japanese and also given the example of demonstrative pronoun in both of language. We also found some of contrastive study of demonstrative pronuon in English and Japanese. As seemingly simple and straightforward constructions, demonstratives are taught to foreign language learners at a rather early stage in their language instruction. For native speakers of Japanese, English this and that (singular), these and those (plural) seem fairly easy to acquire, just as the Japanese demonstratives ko-, so-, and a- seem like unproblematic constructions for native speakers of English. However, language teachers often find that even fairly advanced learners of Japanese or English have trouble with many of the less transparent issues surrounding demonsrative usage. Key Words: Demonstrative pronoun, English, Japanese, and Contrastive study.